The Critical Thinking Skills of Junior High School Student on Simple Machines - Ramadhani, Firda Amelia; Nurita, Tutut (International Journal of Education and Teaching Zone, 2022)
This study describes students’ critical thinking skills in learning science on simple machines. The method used in this research is descriptive quantitative. The subjects in this study were 34 students from one of the public junior high schools in Surabaya. The data collection method used is a test of critical thinking skills. The essay question sheet consists of five critical thinking skills indicators: interpretation, analysis, inference, evaluation, and explanation. The study’s results showed that the average percentage of students’ critical thinking skills indicators was 20%. The percentage results indicate that the critical thinking skills of one of the public junior high schools in Surabaya are classified as very poor with the standard reference assessment criteria.